2002
DOI: 10.1034/j.1600-0560.2002.290605.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of polo‐like kinase (PLK1) in thin melanomas: a novel marker of metastatic disease

Abstract: Our results suggest that PLK1 expression in thin melanomas is a reliable marker to identify patients at high risk for metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
102
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(109 citation statements)
references
References 23 publications
(35 reference statements)
6
102
0
1
Order By: Relevance
“…This hypothesis matches well with observations that PLK1 expression is a survival parameter in oesophageal carcinoma (Tokumitsu et al, 1999), lung carcinoma (Wolf et al, 1997) and squamous cell carcinoma of head and neck (Knecht et al, 1999), and serves as a marker for metastatic disease in malignant melanoma (Kneisel et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This hypothesis matches well with observations that PLK1 expression is a survival parameter in oesophageal carcinoma (Tokumitsu et al, 1999), lung carcinoma (Wolf et al, 1997) and squamous cell carcinoma of head and neck (Knecht et al, 1999), and serves as a marker for metastatic disease in malignant melanoma (Kneisel et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Studies on the expression of PLK1 have been performed on carcinomas of lung (Wolf et al, 1997), head and neck (Knecht et al, 1999), oesophagus and stomach (Tokumitsu et al, 1999), skin (Kneisel et al, 2002), breast , brain (Dietzmann et al, 2001), endometrium and ovary (Takai et al, 2001a, b). All studies consistently reported an overexpression of PLK1 in the respective tumour tissue compared to the corresponding nontransformed tissue of origin.…”
mentioning
confidence: 99%
“…Plk1 is overexpressed in a range of human tumors, including prostate tumors, ovarian carcinomas, hepatoblastomas and melanomas, and Plk1 overexpression was shown to coincide with bad prognosis (Kneisel et al, 2002;Weichert et al, 2004a, b;Yamada et al, 2004). Therefore, Plk1 is useful as a prognostic marker for outcome of disease.…”
Section: Plk1 and Cancermentioning
confidence: 99%
“…The human Plk1 was identified on basis of its high expression levels in rapidly proliferating cells (Holtrich et al, 1994). More recent data have suggested that elevated Plk1 expression in the primary tumor is associated with an unfavorable clinical outcome (Knecht et al, 1999;Kneisel et al, 2002), and experimental silencing of Plk1 has been shown to inhibit proliferative capacity of tumor cells (Spa¨nkuch-Schmitt et al, 2002;Elez et al, 2003). Efficient tumor cell cycle arrest at the G 2 /M boundary following IR exposure requires intact function of the tumor-suppressor protein BRCA1 (Scully and Livingston, 2000), and here we report that the mechanism may involve repression of PLK gene expression.…”
mentioning
confidence: 99%